(82) The Current Development in the Methodology and Applications of Operations Research: Obstacles and Prospects in Developing Countries / التطور الحالي في منهجية وتطبيقات بحوث العمليات : العقبات والافاق في الدول النامية - Amani Omar; Afaf Fouad; Saleh El Adawy (National Planning Institute،, 2018)
November 1993.